Global COVID-19 Vaccine Inequity: Failures in the First Year of Distribution and Potential Solutions for the Future - Pilkington, Victoria; Keestra, Sarai Mirjam; Hill, Andrew (Frontiers in Public Health, 2022)
Within the first year of distribution of vaccines against COVID-19, high-income countries (HICs) have achieved vaccination rates of 70-80%, whilst low-income countries (LICs) have only vaccinated 4-5%. This disparity in access has been one of the greatest failures of international cooperation during the SARS-CoV-2 pandemic. Global COVID-19 vaccine inequity affects us all, with ongoing risk of new variants emerging until global herd immunity is strengthened. The current model of global vaccine distribution is based on financial competition for limited vaccine supplies, resulting in HICs getting first access to vaccines, with LICs being forced to rely on voluntary donations through schemes like COVAX. Pharmaceutical companies own the intellectual property (IP) rights for COVID-19 vaccines, allowing them to control manufacturing, distribution, and pricing. However, the pharmaceutical industry did not develop these vaccines alone, with billions of dollars of public funding being instrumental in their discovery and development. Solutions already exist. The next step in equitable scale up of manufacture and distribution worldwide is equitable knowledge sharing and technology transfer. The WHO centralised technology transfer hub would facilitate international cooperation. Investments made into developing this infrastructure benefit the COVID-19 response whilst promoting future pandemic preparedness. Whilst globally there is majority support for waivers of IP to facilitate this next step, key opponents blocking this move include the UK and other European countries which host large domestic pharmaceutical industries. A nationalistic approach is not effective during a global pandemic. International cooperation is essential to achieve global goals against COVID-19.